ALTRUISME MULTIDIMENSI DALAM ERA DIGITAL: TRANSFORMASI SPIRITUALITAS DAN SOLIDARITAS SOSIAL MELALUI SEDEKAH ONLINE - Nurlaili Adkhi Rizfa Faiza; Vina Septiana Permatasari; Ita Marianingsih (NUANSA: Jurnal Penelitian Ilmu Sosial dan Keagamaan Islam, 2025)
Digital transformation has significantly reshaped Islamic philanthropy practices, particularly in the realm of charity (sadaqah). This article explores online giving as a form of multidimensional altruism that encompasses spiritual, social, economic, and psychological dimensions. Employing a qualitative-descriptive approach through content analysis and literature review, this study examines the role of social media, Muslim influencers, and digital platforms such as Kitabisa.com in shaping the culture of charitable giving among digital Muslim communities. The findings reveal that online charity serves not only as an efficient tool for wealth distribution but also as a contemporary medium for expressing practical spirituality and fostering new forms of cross-boundary social solidarity. However, the transformation also brings ethical and spiritual challenges, particularly concerning intention and authenticity of giving in automated or publicly exposed systems. This article advocates for a reflective approach to the design of Islamic philanthropic technologies to ensure that they remain spiritually meaningful as well as functionally effective.